A Primary Care Provider’s Guide to Social Justice, the Right to Care, and the Barriers to Access After Spinal Cord Injury - Kuemmel, Angela (Top Spinal Cord Inj Rehabil, 2020)
People living with spinal cord injury (SCI) face numerous barriers to primary care. This article identifies these barriers as social justice issues to emphasize their significance and the inequality of primary care received by people with SCI. Primary care providers have a responsibility to provide equal and accessible care to all patients and to remediate any obstacles to care. Understanding the well-documented barriers of competence, physical, policy and procedural, communication, and attitudes impacting primary care for people with SCI will bring much-needed awareness and opportunity for meaningful change. This article is a call to action for social justice within primary care and provides helpful recommendations for removing and addressing barriers. Better health care outcomes for people with SCI are possible if primary care physicians and providers become social justice advocates for their patients with SCI.